2022
DOI: 10.1590/fst.19122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical and functional components of different indica brown and germinated rice

Abstract: Nowadays brown rice (BR) and germinated brown rice (GBR) have aroused great interest of consumers, due to the higher nutrition compared with polished rice. In this study, the nutritional and bioactive compositions of BR and GBR samples prepared by 6 early indica rice cultivars and 12 middle indica rice cultivars from three producing areas were investigated. The free amino acid (215.75 mg/100 g), γ-aminobutyric acid (18.04 mg/100 g) and ferulic acid (195.9 μg/ g) content in early indica rice cultivars after ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…19 We also optimized GABA accumulation via PLT. 20 The present study extends those enzyme process findings, delving deeper into PLT's potential effects on GBR starch composition. In addition, other research teams have performed related studies on PLT with similar findings, including with brown rice 16 and green lentils.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…19 We also optimized GABA accumulation via PLT. 20 The present study extends those enzyme process findings, delving deeper into PLT's potential effects on GBR starch composition. In addition, other research teams have performed related studies on PLT with similar findings, including with brown rice 16 and green lentils.…”
Section: Introductionsupporting
confidence: 71%
“…In prior research, our team demonstrated that PLT enhances the activity of internal enzymes in GBR, including α ‐amylase, amylase and glutamate decarboxylase 19 . We also optimized GABA accumulation via PLT 20 . The present study extends those enzyme process findings, delving deeper into PLT's potential effects on GBR starch composition.…”
Section: Introductionsupporting
confidence: 62%
“…Among them, n-nonanal has a strong grease gas [ 16 ]. (E)-2-Octenal has the aroma of fat and meat [ 17 ], 2-pentyl-furan has the smell of beans and earth grass [ 18 ], alpha-phellandrene has the smell of peppermint and slight citrus [ 19 ], (E)-2-heptenal has the smell of fat [ 20 ], 2-hexanol has the strong smell of grass [ 21 ], butanal has a suffocating smell, and 1,4-dioxane has the smell of ether [ 22 ]. These VOCs together constitute the complex smell of SP.…”
Section: Resultsmentioning
confidence: 99%
“…Selenium and niacin composition in brown rice and the vitamin E composition in linseed oil were obtained from refs. [53,54] and ref. [55] , respectively, due to the absence in refs.…”
Section: The Edible Proportion and Nutrient Compositionmentioning
confidence: 99%